Intracellular Molecular Targets and Signaling Pathways Involved in Antioxidative and Neuroprotective Effects of Cannabinoids in Neurodegenerative Conditions - Ana Tadijan; Ignacija Vlašić; Josipa Vlainić; Domagoj Đikić; Nada Oršolić; Maja Jazvinšćak Jembrek (Antioxidants, 2022)
In the last few decades, endocannabinoids, plant-derived cannabinoids and synthetic cannabinoids have received growing interest as treatment options in neurodegenerative conditions. In various experimental settings, they have displayed antioxidative, anti-inflammatory, antiapoptotic, immunomodulatory, and neuroprotective effects. However, due to numerous targets and downstream effectors of their action, the cellular and molecular mechanisms underlying these effects are rather complex and still under discussion. Cannabinoids are able to neutralize free radicals and modulate the production of reactive oxygen species and the activity of antioxidative systems acting on CB1 and CB2 cannabinoid receptors. The activation of CB1 receptors stimulates signaling pathways involved in antioxidative defense and survival (such as the phosphoinositide 3-kinase (PI3K)/Akt, mitogen-activated protein kinase (MAPK), and Nrf2 pathways) and regulates glutamatergic signaling, the activation of N-methyl-D-aspartate (NMDA) receptors, calcium influx, and the induction of Ca2+-regulated signaling cascades, whereas the neuroprotective effects mediated by CB2 receptors are due to the suppression of microglial activation and the release of prooxidative and proinflammatory mediators. This review summarizes the main molecular mechanisms and new advances in understanding the antioxidative and neuroprotective effects of cannabinoids. Because of the plethora of possible pharmacological interventions related to oxidative stress and cannabinoid-mediated neuroprotection, future research should be directed towards a better understanding of the interplay between activated signal transduction pathways and molecular targets with the aim to improve treatment options and efficacy by targeting the endocannabinoid system.